Belowground seed and bud banks play complementary roles in the potential recruitment of dominant macrophyte communities in a Yangtze River-connected floodplain wetland - Chen, Xin-Sheng; Huang, Ying; Cai, Yun-He; Hou, Zhi-Yong; Deng, Zheng-Miao; Li, Feng; Zou, Ye-Ai; Xie, Yong-Hong (Frontiers in Plant Science, 2022)
Both seed and bud banks play important roles in the recruitment and maintenance of macrophyte communities; however, few studies have investigated them simultaneously. We investigated the abundance, species composition, and seasonal patterns of seed and bud banks in two dominant macrophyte communities, Carex and Miscanthus, in the Dongting Lake wetlands. The seed densities of both communities were lower from November (after flooding) to March and increased dramatically before flooding (in May). The bud densities of the two dominant communities peaked in the coldest month of the year (January), decreased markedly in March, and were the lowest before flooding. The seed banks of the two macrophyte communities were mainly composed of annual species and a few perennial species, whereas the bud banks were composed of only dominant perennials. Furthermore, the perennial species present in bud banks did not occur in seed banks. Among the soil variables, the bud densities of both plant communities were negatively associated with soil bulk density, whereas the seed density of the Miscanthus community was positively associated with soil bulk density. Our results suggest that seed and bud banks are complementary in the potential recruitment of macrophyte communities; that is, bud banks regulate the demography of dominant perennials, and seed banks contribute to the recruitment and dispersal of annual species. Given the high abundance of annuals and near absence of the most dominant perennials in the seed bank, the bud banks of dominant perennial species should be more widely used in wetland restoration and management.